A multi-stage structure all-carbon elastic thermal interface material and a preparation method thereof

CN120422518BActive Publication Date: 2026-10-27YANGTZE RIVER DELTA PHYSICS RES CENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510454766.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-11
Publication Date
2026-10-27
Estimated Expiration
2045-04-11

AI Technical Summary

Technical Problem

[0005]针对当前石墨烯基热界面材料不可避免的由聚合物提供弹性,因此导致热界面材料易老化的问题,本发明提出一种多级结构的全碳弹性热界面材料及其制备方法,相比于现有的聚合物热界面材料,本发明的全碳弹性热界面材料寿命增加了三倍以上,在解决老化问题的基础上,通过结构优化,还克服了热界面材料高密度高导热、翘曲结构自适应和低弹性模量的矛盾,对于推进全碳热界面材料的产业化应用具有重要意义

Benefits of technology

(1)本材料无聚合物提供弹性,热界面寿命增加了三倍以上;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120422518B_ABST
    Figure CN120422518B_ABST
Patent Text Reader

Abstract

The application discloses a full-carbon elastic thermal interface material with a multistage structure and a preparation method thereof. The full-carbon elastic thermal interface material is prepared by the following steps: centrifugal spin coating of a mixture of graphene oxide and a polymer mixture with different mass ratios and PVA which can be decomposed under heating conditions to obtain a composite film, and then performing heat treatment on the composite film to obtain a graphene aerogel. Then, the graphene aerogel is sliced, and plasma etching is performed on the slices to etch away the low-graphitized graphene layer on the surface of the material, and then the full-carbon elastic thermal interface material with a multistage structure is obtained by further hot pressing. The thermal interface material prepared by the method has high elasticity, and since the thermal interface material does not contain a polymer, the thermal interface material has good weather resistance, does not become rigid and aged after long-time work, and greatly improves the material performance and service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of thermal interface materials, specifically relating to a multi-level structured all-carbon elastic thermal interface material and its preparation method. Background Technology

[0002] With the continuous advancement of electronic information technology, the improvement of computer performance, and the emergence of new products such as wearable devices, the functional integration of CPUs is constantly increasing, and they are showing a trend towards miniaturization. This trend has led to a gradual reduction in the heat dissipation space of electronic devices, while the heat generated is constantly increasing, resulting in a rising demand for heat dissipation. Traditional thermal interface materials, such as silicone grease, are gradually failing to meet the heat dissipation requirements of high-performance chips, becoming one of the important problems restricting the development of high-performance chips. In addition, thermal interface materials also have broad application prospects in fields such as 5G, consumer electronics, automotive electronics, wearable devices, and the Internet of Things.

[0003] Graphene is a two-dimensional carbon nanomaterial with extremely high electron mobility and thermal conductivity. Its thermal conductivity is far higher than that of traditional thermally conductive materials such as copper and silicone grease, making it an ideal choice for preparing high-performance thermal interface materials. Graphene-based thermal interface materials primarily use graphene as the thermally conductive framework and fillers such as epoxy resin, silicone oil, silicone rubber, and polyurethane as the elastic matrix, forming a vertically oriented thermal interface structure through specific fabrication processes. Fabrication methods include wrinkle orientation and stacking methods. After vertically oriented graphene, polymer fillers are introduced, providing elasticity to the carbon framework and reducing surface roughness in the chip and heat sink.

[0004] Despite the significant performance advantages and promising applications of graphene-based thermal interface materials, several challenges remain in their research and application: existing carbon-based thermal interface materials still require polymers as a source of material elasticity. However, polymers exhibit poor weather resistance, and after prolonged operation, they harden and age, significantly reducing material performance and lifespan. Summary of the Invention

[0005] To address the issue that current graphene-based thermal interface materials inevitably rely on polymers for elasticity, leading to easy aging, this invention proposes a multi-level structured all-carbon elastic thermal interface material and its preparation method. Compared to existing polymer thermal interface materials, the all-carbon elastic thermal interface material of this invention has a lifespan that is more than three times longer. In addition to solving the aging problem, through structural optimization, it also overcomes the contradictions of high density and high thermal conductivity, warp structure self-adaptation, and low elastic modulus in thermal interface materials. This is of great significance for promoting the industrial application of all-carbon thermal interface materials.

[0006] The all-carbon elastic thermal interface material of this invention is composed of alternating layers of highly graphitized graphene and low-graphitized graphene along the horizontal direction, with a density of 0.3-0.7 g / cm³. 3 The highly graphitized graphene layer includes a continuous first bent structure formed in the middle and skin structures formed at the top and bottom ends; the low-graphitized graphene layer only includes a second bent structure nested with the first bent structure in the middle; the first and second bent structures form the main layer of the thermal interface material of this application. The bent structure is Σ-shaped.

[0007] The highly graphitized graphene layer is formed by continuously stacking highly graphitized graphene sheets, and the low-graphitized graphene layer is formed by continuously stacking low-graphitized graphene sheets. High graphitization is defined as a graphitization degree >96%, and low graphitization is defined as a graphitization degree of 75-90%. The interface material of this invention has a density of 0.7-1 g / cm³. 3 The high-graphitized graphene layer and the low-graphitized graphene layer are continuous in the vertical direction, enabling vertical thermal conductivity with a contact thermal resistance of up to 0.03. The continuous bending structure and the nested structure of high and low graphitization successfully solve the problem of excessively high elastic modulus in high-density, high-thermal-conductivity interface materials. In addition, the aerogel structure of high and low graphitization layers, the flexibility of the large number of SP3 structures inside the low-graphitized graphene structure, and the excellent flexibility and lubricity of the high-graphitized part of the skin can provide the material with adaptive filling of elastic warping structure and friction microstructure, effectively reducing contact thermal resistance.

[0008] The thickness of the all-carbon elastic thermal interface material described in this invention is generally 0.2-0.5 mm, of which the thickness of the skin layer is 1-5 μm.

[0009] To construct the aforementioned high-density, high-thermal-conductivity, self-adaptive warp structure, and low-elastic-modulus thermal interface material, this invention introduces, on the one hand, a roller to construct an alternating stacked structure of highly oriented high and low graphitization layers; on the other hand, a PVA layer is introduced to construct a gas dissipation channel, preventing the delamination of the high and low graphitization layers by gas expansion during heat treatment; finally, pressure is released through precise hot pressing to construct a continuous bending structure. Specifically, this invention includes the following steps: (1) A centrifugal spin coating method is used. The coating is dropped into a horizontally arranged centrifugal drum. Under the action of centrifugal force, a first composite layer with a thickness of 20-80 nm, a second composite layer with a thickness of 5-10 nm, and a PVA layer with a thickness of 5-50 nm are continuously spin-coated on the inner wall of the centrifugal drum. The coating of the first composite layer is composed of graphene oxide and polymer in a mass ratio of 3:7-8:2, and the coating of the second composite layer is composed of graphene oxide and polymer in a mass ratio of 1:10-2:8. The polymer is one or more of polyacrylonitrile, polyimide, furan resin, phenolic resin, and lignin. The first composite layer is used to prepare a high thermal conductivity framework, which can obtain highly graphitized (>96%) graphene at high temperatures. The second composite layer is used to prepare a high thermal conductivity elastic structure, which can obtain graphene with a relatively low degree of graphitization at high temperatures, with a graphitization of 75-90%. The centrifugal spin coating method can make the obtained graphene oriented. The oriented structure increases the orderliness of molecular arrangement, promotes molecular directional fusion, and increases the degree of graphitization. Nanoscale-thick, highly graphitized carbon materials become more slippery due to reduced interlayer interactions, thus exhibiting flexibility. As graphitization decreases, interlayer interactions increase, and the material exhibits elasticity.

[0010] (2) Repeat step 1 multiple times to obtain a composite film consisting of alternating stacks of the first composite layer, the second composite layer, and the PVA layer.

[0011] (3) The above composite membrane was hot-pressed in a nitrogen atmosphere at 270-300℃ with a pressure of 1-5 MPa, and then heat-treated in an argon atmosphere in a confined space at 2700-3000℃ to obtain graphene aerogel with a density of 0.2-0.5 g / cm³. 3 In this process, the polymer and PVA layers completely decompose at high temperatures. During the PVA decomposition process, a gas escape channel is created, which can suppress the delamination of structural units and enable the macroscopic material to form an arched airbag structure.

[0012] (4) Cut the above graphene aerogel into slices perpendicular to the graphene orientation direction, with a thickness of 0.2-0.5 mm.

[0013] (5) The upper and lower surfaces of the slice are treated with plasma to expose the uniformly vertically oriented graphene structure. Then, the low-graphite graphene on the upper and lower surfaces of the slice is etched away to form a skin composed of a high-graphite layer.

[0014] (6) Place the plasma-treated slices in an argon atmosphere and sinter at a high temperature of 2000-3000℃; the surface of the plasma-treated graphene is damaged, but it can be repaired by high-temperature sintering.

[0015] (7) Press the treated slices at a pressure of 0.2-2 MPa for 2-20 seconds. The density of the resulting product is 0.7-1 g / cm³. 3 The highly graphitized layer of the cortex changes from a vertical direction to a horizontal direction, and the high and low graphitized layers of the main body form a nested, bent structure.

[0016] The third technical solution of the present invention provides another method for preparing a multi-level structured all-carbon elastic thermal interface material: (1) A centrifugal spin coating method is adopted, in which the coating is dripped into a horizontally arranged centrifugal drum, and under the action of centrifugal force, a first composite layer of 2-5 nm, a second composite layer of 20-80 nm, a third composite layer of 2-5 nm and a PVA layer of 5-50 nm are continuously spin coated on the inner wall of the centrifugal drum in sequence; the coating of the first composite layer is composed of graphene oxide and polymer in a mass ratio of 1:10-3:7, the coating of the second composite layer is composed of graphene oxide and polymer in a mass ratio of 3:7-8:2, and the coating of the third composite layer is composed of graphene oxide and polymer in a mass ratio of 1:10-2:8, wherein the polymer is one or more of polyacrylonitrile, polyimide, furan resin, phenolic resin and lignin.

[0017] (2) Repeat step 1 multiple times until the thickness meets the product requirements to obtain a composite film consisting of alternating stacks of the first composite layer, the second composite layer, the third composite layer, and the PVA layer.

[0018] (3) The above composite membrane was hot-pressed in a nitrogen atmosphere at 270-300℃ with a pressure of 1-5 MPa, followed by heat treatment in an argon atmosphere under confined space at 2700-3000℃ to obtain graphene aerogel with a density of 0.2-0.5 g / cm³. 3 .

[0019] (4) Cut the above graphene aerogel into slices perpendicular to the graphene orientation direction, with a thickness of 0.2-0.5 mm.

[0020] (5) The upper and lower surfaces of the slice are treated with plasma to expose the uniformly vertically oriented graphene structure. Then, the low-graphite graphene on the upper and lower surfaces of the slice is etched away to form a skin composed of a high-graphite layer.

[0021] (6) Place the plasma-treated slices in an argon atmosphere and sinter at a high temperature of 2000-3000℃; plasma treatment will damage the surface structure of the material, which needs to be repaired by high temperature.

[0022] (7) Press the treated slices at a pressure of 0.2-5 MPa for 2-20 seconds. The density of the resulting product is 0.7-1 g / cm³. 3The highly graphitized layer of the cortex changes from a vertical direction to a horizontal direction, and the high and low graphitized layers of the main body form a nested, bent structure.

[0023] In the preparation process of the two thermal interface materials mentioned above, continuous spin coating means that after the first coating is sprayed, the second coating is sprayed immediately. Thus, the second coating is laminated before the first film is completely dry, and the two films are effectively fused, which is conducive to continuous heat conduction channels.

[0024] In the preparation of the two thermal interface materials mentioned above, the low-graphitized material, due to its greater presence of defects, disordered regions, and dangling bonds, exhibits a more active surface and readily reacts with reactive particles in the plasma. In contrast, the high-graphitized material, with its structure approaching an ideal graphite lattice, displays higher chemical and thermal stability and is less prone to reacting with reactive species such as ions and free radicals in the plasma. Furthermore, the high-graphitized material possesses better electrical conductivity, effectively shielding against the effects of plasma and thus reducing the etching rate; while the low-graphitized material, due to its poor conductivity, is more significantly affected during plasma etching. Therefore, in the plasma treatment process of step 5, the low-graphitized material typically exhibits a faster etching rate and greater etching selectivity than the high-graphitized material during plasma etching. During plasma etching, less of the high-graphitized layer is etched away, while more of the low-graphitized layer is etched away, resulting in a skin layer formed by the extension of some of the high-graphitized graphene sheets to the upper and lower sides. The graphene density in this skin layer is reduced by half, increasing its flexibility and interstitial filling capacity.

[0025] In the preparation process of the above two thermal interface materials, the slicing method is one of laser etching slicing and wire cutting slicing.

[0026] The beneficial effects of this invention are: (1) This material does not contain polymers to provide elasticity, and the thermal interface life is increased by more than three times; (2) The design of the core structure inside the structural unit provides good support, elasticity and filling without affecting the heat conduction path; (3) The density of the thermal interface skin is lower than that of the middle layer, and only the part with a high degree of graphitization is retained. It has good flexibility, lubricity and filling performance, which greatly reduces the contact thermal resistance. Attached Figure Description

[0027] Figure 1 This is a physical image of the present invention.

[0028] Figure 2 This is a schematic diagram illustrating the effect of step 6 of the present invention.

[0029] Figure 3 (a) is a SEM image of the cross-section of Example 1. Figure 3 (b) is a SEM image of the upper surface of Example 1.

[0030] Figure 4 This is a partial enlarged view of Example 1.

[0031] Figure 5 The value represents the compressive strain after multiple stress cycles in Example 1. Detailed Implementation

[0032] The following examples are provided to further illustrate the present invention and are intended to explain the invention, not to limit its scope. Unless otherwise specified, all figures are expressed in parts by weight and weight percentages.

[0033] Unless otherwise specified, the raw materials used in this invention are all conventional commercially available products; unless otherwise specified, the methods used in this invention are all conventional methods in the field.

[0034] The rotary spin coating described in this invention can be referenced from existing technologies such as 202410407489.8.

[0035] The contact thermal resistance described in this invention is tested using the TIM-Tester thermal interface material testing system.

[0036] The embodiments of the present invention will be further described below with reference to several examples.

[0037] It should be understood that the described embodiments are merely some, not all, of the embodiments in this application. All other embodiments obtained by those skilled in the art based on the embodiments in this application without inventive effort are within the scope of protection of this application.

[0038] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms “a,” “the,” and “the” used in the embodiments of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.

[0039] Example 1 (1) Graphene oxide and polyacrylonitrile were mixed evenly in a mass ratio of 3:7 to obtain the first coating; graphene oxide and polyacrylonitrile were mixed evenly in a mass ratio of 1:10 to obtain the second coating. PVA was dispersed in deionized water to prepare a third coating with a mass fraction of 1%.

[0040] (2) The first coating, the second coating and the third coating are sequentially dripped into the horizontally arranged centrifugal drum, and the metering of each injection is controlled. Under the action of centrifugal force, a 20 nm first composite layer, a 10 nm second composite layer and a 5 nm PVA layer are sequentially formed on the inner wall of the centrifugal drum.

[0041] (3) Repeat step 2 multiple times to obtain a composite membrane with a thickness of 2 cm.

[0042] (4) The above composite membrane was hot-pressed in a nitrogen atmosphere at 270°C (pressure 1 MPa), followed by heat treatment in an argon atmosphere at 2700°C in a confined space to obtain a membrane with a thickness of 5 cm and a density of 0.25 g / cm³. 3 Graphene aerogel.

[0043] (5) Cut the above graphene aerogel into slices with a thickness of 0.2 mm.

[0044] (6) The upper and lower surfaces of the slice are treated with plasma to expose the uniformly vertically oriented graphene structure. Then, the low-graphite graphene on the upper and lower surfaces of the slice is etched away to form a skin composed of a high-graphite layer.

[0045] (7) The plasma-treated slices were placed in an argon atmosphere and sintered at 3000℃. (8) Press the processed slices at a pressure of 0.2 MPa for 20 seconds.

[0046] The resulting interface material has an overall thickness of 0.17 mm and a density of 0.8 g / cm³. 3 Its cross-sectional and surface views are as follows: Figure 3 As shown, from Figure 3 As can be seen, the central main layer has a continuous Σ-shaped bent structure. Based on the composite method, we can determine that it is a bent structure formed by nesting a first bent structure formed by a highly graphitized graphene layer and a second bent structure formed by a low-graphitized graphene layer. The skin layer is about 4 μm thick and extends basically horizontally. It is formed by the high-graphitized graphene layer under pressure.

[0047] Figure 4 The enlarged view of the bending point shows that under micro-pressure, the graphene only undergoes delamination without breaking, releasing its elastic modulus while maintaining a continuous thermal conductivity path.

[0048] Tests showed that the contact thermal resistance of this embodiment is 0.06 K·cm2 / W, the service life is up to 3000 hours, and it still maintains perfect strain recovery after multiple cycles, indicating that the material has good elasticity and stability.

[0049] Example 2 (1) Graphene oxide and polyimide in a mass ratio of 8:2 are mixed evenly to obtain the first coating; graphene oxide and polyimide in a mass ratio of 2:8 are mixed evenly to obtain the second coating; and PVA is dispersed in deionized water to prepare a third coating with a mass fraction of 1%.

[0050] (2) The first coating, the second coating and the third coating are sequentially dripped into the horizontally arranged centrifugal drum, and the metering of each injection is controlled. Under the action of centrifugal force, an 80 nm first composite layer, a 5 nm second composite layer and a 50 nm PVA layer are sequentially formed on the inner wall of the centrifugal drum.

[0051] (3) Repeat step 2 multiple times to obtain a composite membrane with a thickness of 1.2 cm.

[0052] (4) The above composite membrane was hot-pressed in a nitrogen atmosphere at 300°C (pressure 5 MPa), followed by heat treatment in an argon atmosphere at 3000°C in a confined space to obtain a membrane with a thickness of 4 cm and a density of 0.2 g / cm³. 3 Graphene aerogel.

[0053] (5) Cut the above graphene aerogel into slices with a thickness of 0.5 mm.

[0054] (6) The upper and lower surfaces of the slice are treated with plasma to expose the uniformly vertically oriented graphene structure. Then, the low-graphite graphene on the upper and lower surfaces of the slice is etched away to form a skin composed of a high-graphite layer.

[0055] (7) The plasma-treated slices were placed in an argon atmosphere and sintered at 2000℃. (8) Press the processed slices at a pressure of 4 MPa for 20 seconds. The highly graphitized layer of the cortex changes from vertical to horizontal, and the high and low graphitized layers of the main body form a nested, bent structure. The overall thickness of the material is 0.37 mm, and the density is 1 g / cm³. 3 The cortex thickness is approximately 3 μm.

[0056] The contact thermal resistance of this embodiment is 0.1 K·cm² / W, as tested. The service life exceeds 3000 hours.

[0057] Example 3 (1) Graphene oxide and furan resin in a mass ratio of 1:10 are mixed evenly to obtain the first coating; graphene oxide and furan resin in a mass ratio of 3:7 are mixed evenly to obtain the second coating; graphene oxide and phenolic resin in a mass ratio of 1:10 are mixed evenly to obtain the third coating; PVA is dispersed in deionized water to prepare a fourth coating with a mass fraction of 1%.

[0058] (2) The first coating, the second coating, the third coating and the fourth coating are sequentially dripped into the horizontally arranged centrifugal drum. The metering of each injection is controlled. Under the action of centrifugal force, a 2 nm first composite layer, a 20 nm second composite layer, a 2 nm third composite layer and a 5 nm PVA layer are sequentially formed on the inner wall of the centrifugal drum.

[0059] (3) Repeat step 2 to obtain a composite membrane with a thickness of 3 cm.

[0060] (4) The above composite membrane was hot-pressed in a nitrogen atmosphere at 270°C (pressure 1 MPa), followed by heat treatment in an argon atmosphere at 2700°C in a confined space to obtain a membrane with a thickness of 4 cm and a density of 0.5 g / cm³. 3 Graphene aerogel.

[0061] (5) Cut the above graphene aerogel into slices with a thickness of 0.4 mm.

[0062] (6) The upper and lower surfaces of the slice are treated with plasma to expose the uniformly vertically oriented graphene structure. Then, the low-graphite graphene on the upper and lower surfaces of the slice is etched away to form a skin composed of a high-graphite layer.

[0063] (7) The plasma-treated slices were placed in an argon atmosphere and sintered at a high temperature of 2500℃; (8) Press the processed slices at a pressure of 3 MPa for 15 seconds. The highly graphitized layer of the cortex changes from a vertical to a horizontal direction, and the high and low graphitized layers of the main body form a nested, bent structure. The overall thickness of the material is 0.28 mm, and the density is 0.7 g / cm³. 3 The cortex thickness is approximately 5 μm.

[0064] The contact thermal resistance of this embodiment is 0.04 K·cm² / W, as tested. The service life exceeds 3000 hours.

[0065] Example 4 (1) Graphene oxide and lignin in a mass ratio of 3:7 are mixed evenly to obtain the first coating; graphene oxide and lignin in a mass ratio of 8:2 are mixed evenly to obtain the second coating; graphene oxide and polyimide in a mass ratio of 2:8 are mixed evenly to obtain the third coating; PVA is dispersed in deionized water to prepare a fourth coating with a mass fraction of 1%.

[0066] (2) The first coating, the second coating, the third coating and the fourth coating are sequentially dripped into the horizontally arranged centrifugal drum. The metering of each injection is controlled. Under the action of centrifugal force, a 5nm first composite layer, an 80nm second composite layer, a 5nm third composite layer and a 50nm PVA layer are sequentially formed on the inner wall of the centrifugal drum.

[0067] (3) Repeat step 2 to obtain a composite membrane with a thickness of 2.15 cm.

[0068] (4) The above composite membrane was hot-pressed in a nitrogen atmosphere at 300°C (pressure 5 MPa), followed by heat treatment in an argon atmosphere at 3000°C in a confined space to obtain a membrane 5 cm thick with a density of 0.3 g / cm³. 3 Graphene aerogel.

[0069] (5) Cut the above graphene aerogel into slices with a thickness of 0.5 mm.

[0070] (6) The upper and lower surfaces of the slice are treated with plasma to expose the uniformly vertically oriented graphene structure. Then, the low-graphite graphene on the upper and lower surfaces of the slice is etched away to form a skin composed of a high-graphite layer.

[0071] (7) The plasma-treated slices were placed in an argon atmosphere and sintered at 2000℃. (8) Press the processed slices at a pressure of 5 MPa for 20 seconds. The highly graphitized layer of the cortex changes from a vertical to a horizontal direction, and the high and low graphitized layers of the main body form a nested, bent structure. The overall thickness of the material is 0.3 mm, and the density is 0.7 g / cm³. 3 The cortex thickness is approximately 1 μm.

[0072] The contact thermal resistance of this embodiment is 0.05 K·cm² / W, as tested. The service life exceeds 3000 hours.

[0073] The above embodiments detail the structure, features, and effects of the present invention. The above descriptions are merely preferred embodiments of the present invention. Any changes made in accordance with the concept of the present invention, or equivalent embodiments modified to have equivalent variations, shall still fall within the scope of protection of the present invention if they do not exceed the scope covered by the specification.

Claims

1. A multi-level structured all-carbon elastic thermal interface material, characterized in that, It is composed of alternating layers of highly graphitized and low-graphitized graphene along the horizontal direction, with a density of 0.7-1 g / cm³. 3 The highly graphitized graphene layer includes a continuous first bent structure formed in the middle and skin structures formed at the top and bottom ends; the low-graphitized graphene layer only includes a second bent structure nested with the first bent structure in the middle; the first and second bent structures form the main layer of the thermal interface material; the bent structure is Σ-shaped; the highly graphitized graphene layer is formed by continuously overlapping highly graphitized graphene sheets, and the low-graphitized graphene layer is formed by continuously overlapping low-graphitized graphene sheets; highly graphitized means graphitization degree >96%, and low-graphitized means graphitization degree 75-90%.

2. The all-carbon elastic thermal interface material according to claim 1, characterized in that, The thickness of the cortex is 1-5 μm.

3. A method for preparing a multi-level structured all-carbon elastic thermal interface material as described in claim 1, characterized in that, It includes the following steps: (1) A centrifugal spin coating method is used, in which the coating is dripped into a horizontally arranged centrifugal drum, and under the action of centrifugal force, a first composite layer with a thickness of 20-80 nm, a second composite layer with a thickness of 5-10 nm, and a PVA layer with a thickness of 5-50 nm are continuously spin coated on the inner wall of the centrifugal drum in sequence; the coating of the first composite layer is composed of graphene oxide and polymer in a mass ratio of 3:7-8:2, and the coating of the second composite layer is composed of graphene oxide and polymer in a mass ratio of 1:10-2:8; the polymer is one or more of polyacrylonitrile, polyimide, furan resin, phenolic resin, and lignin; (2) Repeat step 1 multiple times to obtain a composite film consisting of alternating stacks of the first composite layer, the second composite layer, and the PVA layer; (3) The above composite film was hot-pressed in a nitrogen atmosphere at 270-300℃, and then heat-treated in an argon atmosphere in a confined space at 2700-3000℃ to obtain graphene aerogel with a density of 0.2-0.5 g / cm³. 3 ; (4) Cut the above graphene aerogel into slices perpendicular to the graphene orientation direction, with a thickness of 0.2-0.5 mm; (5) The upper and lower surfaces of the slice are treated with plasma to expose the uniformly vertically oriented graphene structure. Then, the low-graphite graphene on the upper and lower surfaces of the slice is etched away to form a skin composed of a high-graphite layer. (6) Place the plasma-treated slices in an argon atmosphere and sinter at a high temperature of 2000-3000℃; (7) Press the treated slices at a pressure of 0.2-2 MPa for 2-20 seconds. The density of the resulting product is 0.7-1 g / cm³. 3 .

4. A method for preparing a multi-level structured all-carbon elastic thermal interface material as described in claim 1, characterized in that, It includes the following steps: (1) A centrifugal spin coating method is adopted, in which the coating is dripped into a horizontally arranged centrifugal drum, and under the action of centrifugal force, a first composite layer of 2-5 nm, a second composite layer of 20-80 nm, a third composite layer of 2-5 nm and a PVA layer of 5-50 nm are continuously spin coated on the inner wall of the centrifugal drum in sequence; the coating of the first composite layer is composed of graphene oxide and polymer in a mass ratio of 1:10-3:7, the coating of the second composite layer is composed of graphene oxide and polymer in a mass ratio of 3:7-8:2, and the coating of the third composite layer is composed of graphene oxide and polymer in a mass ratio of 1:10-2:8, wherein the polymer is one or more of polyacrylonitrile, polyimide, furan resin, phenolic resin and lignin; (2) Repeat step 1 multiple times to obtain a composite film consisting of alternating stacks of the first composite layer, the second composite layer, the third composite layer, and the PVA layer; (3) The above composite film was hot-pressed in a nitrogen atmosphere at 270-300℃, and then heat-treated in an argon atmosphere in a confined space at 2700-3000℃ to obtain graphene aerogel with a density of 0.2-0.5 g / cm³. 3 ; (4) Cut the above graphene aerogel into slices perpendicular to the graphene orientation direction, with a thickness of 0.2-0.5 mm; (5) The upper and lower surfaces of the slice are treated with plasma to expose the uniformly vertically oriented graphene structure. Then, the low-graphite graphene on the upper and lower surfaces of the slice is etched away to form a skin composed of a high-graphite layer. (6) Place the plasma-treated slices in an argon atmosphere and sinter at a high temperature of 2000-3000℃; (7) Press the treated slices at a pressure of 0.2-2 MPa for 2-20 seconds. The density of the resulting product is 0.7-1 g / cm³. 3 .

5. The preparation method according to claim 3 or 4, characterized in that, The slicing method is laser etching or wire cutting.

6. The preparation method according to claim 3 or 4, characterized in that, The pressure for hot pressing is 1-5 MPa.

Citation Information

Patent Citations

  • Method for preparing self-supporting graphite film and soft X-ray detector

    CN118239483A

  • Composite material with packing in orientated arrangement and preparation method of composite material

    CN106810876A

  • Heat-conducting product with layered fold structure

    CN108531143A